Code-to-code comparisons on spatial solution capabilities and performances between nTRACER and the standalone IDT solver of APOLLO3®. (May 2018) - Ban, Young Suk; Masiello, Emiliano; Lenain, Roland; Joo, Han Gyu; Sanchez, Richard
Abstract: In order to examine the performance of two deterministic codes, nTRACER and the standalone developing version of the IDT solver of APOLLO3®, problems from 2D single assembly to 3D full core were computed with the same macroscopic cross-section library, so as to suppress the effects of physical modeling and to allow a direct comparison in terms of methodology, code architecture and performances. The problems we considered include cases for which the codes were not optimized in their initial design, allowing thus to analyze the potential for generalization and/or estimate possible improvements to broaden the scope of application of the codes.